Sports and mental health in Malaysia: an emerging focus - Eugene Koh Boon Yau; Tze, Nicholas Ping Pang; Mohd Amiruddin Mohd Kassim; Rebecca Sook Kwan Wong (Hogrefe, 2025)
Since its independence in 1957, Malaysia has garnered varying degrees of success in multiple sports, notably but not limited to squash, badminton, swimming, sepak takraw, and field hockey. In recent years, the intersection of sports and mental health has garnered increased attention globally, including in Malaysia. This growing focus reflects a broader recognition of the critical role mental health plays in the overall well-being and performance of athletes [1]. Only recently has there been more attention drawn to the instrumental role of psychiatry and psychiatrists together with the allied health professionals that constitute the profession, both in remediating mental health issues, and in promoting overall wellness and as a branch of lifestyle medicine. This has culminated in the completion of training of the first two qualified psychiatrists with a certificate of additional training in sports psychiatry. This discussion explores various initiatives, current services, research advancements, and recommendations to further promote mental health in sports within the Malaysian context.